Pengaruh Edukasi Kesehatan Terhadap Kecemasan Lansia Tentang Penularan Corona Virus Disease (Covid 19) - Meriem Meisyaroh Syamson; Abd Hayat Fattah; Sulkifli Nurdin (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; the age factor and lack of knowledge can be a cause of anxiety and worry, excessive fear that disturbs and reduces the immunity of the human body so that it is very susceptible to exposure or catching COVID-19. Destination; know the effect of health education on elderly anxiety about the transmission of the coronavirus disease (covid 19). Method; using a quasi-experimental research design, namely one group pretest-posttest, which is to determine the effect of elderly anxiety on the transmission of Corona Virus Disease (COVID 19) before and after counseling. Result; that there is a significant difference between anxiety about Covid-19 transmission before and after education and there is an effect of health education on family anxiety p (0.013). Conclusion; that there is a significant difference in the frequency of anxiety about COVID-19 before intervention and after the health education intervention